2020
DOI: 10.1088/1361-6501/ab848c
|View full text |Cite
|
Sign up to set email alerts
|

Progress of nanopositioning and nanomeasuring machines for cross-scale measurement with sub-nanometre precision

Abstract: Nanopositioning and nanomeasuring machines (NPM-machines), developed at Technische Universität Ilmenau, have provided high-precision measurement and positioning of objects across ten decades, from 20 pm resolution up to 200 mm measuring range. They work on the basis of the error-minimal, extended six degrees of freedom Abbe-comparator principle, with high-precision fibre-coupled laser interferometers and optical or atomic force probes. These machines are suitable not only for measuring but also for positioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Compared to tactile measurement instruments and scanning probe microscopes, CSI and CSM are faster and contactless. Such optical sensors providing high axial and lateral resolution are for example needed for nanopositioning and nanomeasuring technology [9,10] or measurements of surface properties of silica waveguides such as surface roughness [5] and side wall angles [6].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to tactile measurement instruments and scanning probe microscopes, CSI and CSM are faster and contactless. Such optical sensors providing high axial and lateral resolution are for example needed for nanopositioning and nanomeasuring technology [9,10] or measurements of surface properties of silica waveguides such as surface roughness [5] and side wall angles [6].…”
Section: Introductionmentioning
confidence: 99%
“…Calculate the standard deviation s u(y) of the average value of u(y (1) ),u(y (2) ),…,u(y (h) );Standard deviation s ylow of the mean value of y (1) low ,y (2) low ,...,y (h) low ; And the standard deviation s yhigh of the average value of y (1) high ,y (2) high ,...,y…”
Section: Determine the Measurement Model Input Distribution And Proba...mentioning
confidence: 99%
“…In the design and development of the micro/nano coordinate measuring machine (CMM), the measurement framework is used to realize 3D precision measurement, so it is an important part of micro/nano measuring machine. The measurement frame of the CMM is usually formed by three laser interferometers arranged in the X, Y and Z measurement directions and a 3D target mirror that can reflect the laser beam [1]. The 3D target mirror is made up of three plane mirrors bonded together.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with the NPM machines revealed that in addition to the measuring capabilities, their positioning properties are excellent as well. The machines have an enormous position resolution of down to 5 pm, an ultra low position noise, trajectory deviations in the single nanometer range, and virtually no overshoot during changes in direction or when approaching a certain position [36,39]. Therefore, the NPM machines of the Technische Universität Ilmenau are perfect tools for the fabrication of 2D and 3D nanostructures in the size of a wafer.…”
Section: State Of the Artmentioning
confidence: 99%